EMERGING TRENDS IN THERAPEUTIC PEPTIDE PHARMACEUTICALS: PROSPECTS AND PERSPECTIVES - Sangeetha, Nagarajan; Selvamani, Palanisamy; Latha, Subbiah (Journal of Drug Delivery and Therapeutics, 2019)
Over the last few decades, the inclusions of peptide drugs in the pharmaceutical formulation aspects are more contemporary and recurrent. Since peptide moieties for the treatment of various clinical conditions has been started worthwhile since 1930’s. There has been an increasingly sustainable research work regarding the formulation of therapeutic peptides are in the arena, as probably several entities are already in the clinical investigation, where as few more are in the pipeline for clinical indication. In this current discussion, it has been aimed to unleash the potential of therapeutic bioactive peptides and its future prospects, in the area of pharmaceutical formulation. A plinth of area in regard to the, demand for the development of pharmaceutical formulation of bioactive peptides are still need to be uncovered. And hence only we have discussed deeply about the contemporary prospects of the peptide moieties. Keywords: Peptide drugs, pharmaceutical formulation, current trends, clinical implications